Rhodium‐Catalysed Tandem Hydroformylation/Arylation Reaction with Boronic Acids. Issue 6 (18th March 2014) - Almeida, Ana R.; Dias, Roberto D.; Monteiro, Carlos J. P.; Abreu, Artur R.; Gois, Pedro M. P.; Bayon, J. Carles; Pereira, Mariette M.
Abstract A new efficient multicatalytic process involving a single catalyst to promote tandem hydroformylation/arylation reactions is disclosed. The effect of the rhodium ligand was evaluated and the rhodium/triphenylphosphine catalytic system was selected to apply the methodology to different olefins and boronic acids. High yields (up to 89%) and good to excellent isomer ratios (up to 98:2) were achieved using aryl olefins as starting materials. This new methodology allows the preparation of secondary alcohols, from simple olefins, and paves the way for the synthesis of high‐value products, namely vinylindole and anethole derivatives. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>